Gel Formulation from Ethanol Extract of The Leaf of White Guava (Psidium guajava L.) - Rety Setyawaty; Gustin Gustin; Ragil Setiyabudi (Majalah Obat Tradisional, 2021)
White guava is a plant that can grow easily in Indonesia. As a source of vitamin C, white guava leaves have been used as antidiarrheal drugs. Some studies state that white guava leaves contain antioxidants. Aside from having a selling value, white guava leaves are also used as raw materials for facial cosmetics, namely as raw materials for gel. Flavonoids are a large family of plant secondary metabolites that have various and amazing biological functions, including as antioxidants. The study aims to determine the gel preparation formulation of the white guava leaf extract (Psidium guajava L.) as a good antioxidant and the characteristics of the preparation. To extract the active substance in simplicia, maceration is used by using ethanol extract processes. The gel making uses a CMC-Na base. Formulation I uses a concentration of CMC-Na 0.1 gram. Formulation II uses a concentration of CMC-Na 0.3 grams. Formulation III uses a concentration CMC-Na 0.6 gram. The main raw material is 0.2 grams of white guava leaf ethanol extract for each formulation. The maceration process uses 70% ethanol. 250 grams of white guava leaves are used. The yield obtained was 13.92%. The gel product was analyzed organoleptic test, pH test, dispersion test, homogeneity test, and adhesion test. The results showed that the CMC-Na 0.1-grams, 0.3 grams CMC-Na, and 0.6-grams CMC-Na had a distinctive odor of white guava leaves, brownish color, and thick concentration. The gelling product is homogeneous and pH of 6. The formulations under CMC-Na 0.6 grams have good dispersibility. All formulations have good adhesion. The adhesion is more than 4 seconds. The conclusions are the formulation with CMC-Na 0.6 grams fulfills the requirements for topical gel preparation.